Accuracy of cotinine serum test to detect the smoking habit and its association with periodontal disease in a multicenter study (2017)
ABSTRACT: Background: The validity of the surveys on self-reported smoking status is often questioned because smokers underestimate cigarette use and deny the habit. It has been suggested that self-report should be accompanied by a cotinine test. This report evaluates the usefulness of serum cotinine test to assess the association between smoking and periodontal status in a study with a large sample population to be used in studies with other serum markers in epidemiologic and periodontal medicine research. Material and Methods: 578 patients who were part of a multicenter study on blood biomarkers were evaluated about smoking and its relation to periodontal disease. Severity of periodontal disease was determined using clinical attachment loss (CAL). Smoking was assessed by a questionnaire and a blood sample drawn for serum cotinine determination. Results: The optimal cut-off point for serum cotinine was 10 ng/ml. Serum cotinine showed greater association with severity of CAL than self-report for mild-moderate CAL [OR 2.03 (CI95% 1.16-3.53) vs. OR 1.08 (CI95%0.62-1.87) ] advanced periodontitis [OR 2.36 (CI95% 1.30- 4.31) vs. OR 2.06 (CI95% 0.97-4.38) ] and extension of CAL > 3 mm [ OR 1.78 (CI95% 1.16-1.71) vs. 1.37 (CI95% 0.89-2.11)]. When the two tests were evaluated together they were not shown to be better than serum cotinine tests. Conclusions: Self-reported smoking and serum cotinine test ≥ 10ng/ml are accurate,complementary and more reliable methods to assess the patient’s smoking status and could be used in studies evaluating serum samples in large population and multicenter studies. Clinical Relevance: The serum cotinine level is more reliable to make associations with the patient’s periodontal status than self-report questionnaire and could be used in multicenter and periodontal medicine studies.